Effect of range of motion and isometric strengthening exercises on grip strength and hand function in rheumatoid arthritis patients - Bastiana, Yefta Daniel; Tulaar, Angela BM; Hartono, Surjanto; Albar, Zuljasri (Universa Medicina, 2008)
In previous studies, duration of hand exercises in patients with rheumatoid arthritis (RA) had widely varying ranges, from 3 weeks to 4 months. An experimental study was conducted to evaluate the effect of range of motion (ROM) and muscle strengthening exercises for 6 weeks on grip strength and hand function in RA patients. Seventeen patients with chronic RA were randomly assigned to a treatment group and a control group. The treatment group (n=8) was given muscle strengthening exercises and heat therapy using paraffin baths 3 times a week at the hospital and ROM exercises once a day at home for 6 weeks. The control group (n=9) was given only paraffin baths 3 times a week. After 6 weeks, there were significant differences in hand function (p=0.003), right and left grip strength (p=0.000 and p=0.001) and ROM in the interventional group only. ROM and isometric strengthening exercises significantly improved grip strength and hand function in patients with RA, while no impact was found when the patients were given paraffin baths only. In view of the small size of the study population, there is a need for further studies with larger populations.